Does older adults' use of social care influence their healthcare utilisation? A systematic review of international evidence. (17th July 2019) - Spiers, Gemma; Matthews, Fiona E.; Moffatt, Suzanne; Barker, Robert; Jarvis, Helen; Stow, Daniel; Kingston, Andrew; Hanratty, Barbara
Abstract: Improving our understanding of the complex relationship between health and social care utilisation is vital as populations age. This systematic review aimed to synthesise evidence on the relationship between older adults' use of social care and their healthcare utilisation. Ten databases were searched for international literature on social care (exposure), healthcare use (outcome) and older adults (population). Searches were carried out in October 2016, and updated May 2018. Studies were eligible if they were published after 2000 in a high income country, examined the relationship between use of social care and healthcare utilisation by older adults (aged ≥60 years), and controlled for an indicator of need. Study quality and bias were rated using the National Institute of Health (NIH) Quality Assessment Tool for Observational Cohort and Cross‐Sectional Studies. Study data were extracted and a narrative synthesis was conducted. Data were not suitable for quantitative synthesis. Thirteen studies were identified from 12, 065 citations. Overall, the quality and volume of evidence was low. There was limited evidence to suggest that longer lengths of stay in care homes were associated with a lower risk of inpatient admissions. Residents of care homes with onsite nursing had fewer than expected admissions to hospital, compared to people in care homes without nursing, and adjusting for need. Evidence for other healthcare use outcomes was even more limited and heterogeneous, with notable gaps in primary care. We conclude that older adults' use of care homes may moderate inpatient admissions. In particular, the presence of registered nurses in care homes may reduce the need to transfer residents to hospital. However, further evidence is needed to add weight to this conclusion. Future research should build on this evidence and address gaps regarding the influence of community based social care on older adults' healthcare use. A greater focus on primary care outcomes is imperative.